2018
DOI: 10.1364/oe.26.010997
|View full text |Cite
|
Sign up to set email alerts
|

First-order optical spatial differentiator based on a guided-mode resonant grating

Abstract: We present an experimental demonstration of a subwavelength diffraction grating performing first-order differentiation of the transverse profile of an incident optical beam with respect to a spatial variable. The experimental results are in a good agreement with the presented analytical model suggesting that the differentiation is performed in transmission at oblique incidence and is associated with the guided-mode resonance of the grating. According to this model, the transfer function of the grating in the v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 95 publications
(55 citation statements)
references
References 18 publications
0
54
0
Order By: Relevance
“…For practice, simple structures are more preferable, for example by a single layer of resonant metasurface . As an important component for optical processing, the first‐order analog optical spatial differentiator has attracted special attentions . The practicability has been greatly improved in recent works.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…For practice, simple structures are more preferable, for example by a single layer of resonant metasurface . As an important component for optical processing, the first‐order analog optical spatial differentiator has attracted special attentions . The practicability has been greatly improved in recent works.…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, Zhu et al has experimentally realized such an optical differentiation device utilizing the angle sensitive excitation of surface plasmonic polariton on metal films . More recently, Bykov et al and Dong et al separately have showed the similar function using subwavelength gratings . However, the plasmonic approach could not be readily extended for other frequency bands primarily limited by the response of material properties.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations